ASSISTANCE IN DESIGNING THE ENTRANCE TO THE AL MAHIRA ISLAMIC EDUCATION FOUNDATION, BANARAN, SEMARANG AS AN EFFORT TO IMPROVE PUBLIC ATTENTION - Al-Ghin, Majora Nuansa; Saratri Wilonoyudho; RM. Bambang Setyohadi Kuswarna Putra; Dimas Wicaksono; Hari Utama (LPPM ITB AAS Indonesia Surakarta, 2025)
Educational foundations play a strategic role in the provision of formal and non-formal education as a means of improving the quality of the nation's generation. The Al Mahira Islamic Foundation, located in Banaran Village, Sekaran, Gunungpati, is an official institution focused on child development from early childhood through kindergarten. The problem that arose was the foundation's location in an alley, making access to the location difficult for the community and parents of prospective students to recognize. The markers used were still simple banners, considered unattractive and unable to optimally represent the institution's identity. Therefore, it was necessary to design more representative, artistic, and communicative access markers to strengthen the image of the Al Mahira Islamic Foundation while making it easier for the public to find the location. This activity was expected to support the branding of community-based Islamic educational institutions